A Qualitative Study of Health Care Providers' Views on Integrating Oral Health into Prenatal Care. (October 2021) - Adeniyi, A.; Donnelly, L.; Janssen, P.; Jevitt, C.; von Bergman, H.; Brondani, M.
Objective: Providing preventive oral health during prenatal care is a recognized strategy for improving pregnant women's access to oral health care. This study sought to qualitatively explore the views of health care providers in British Columbia (BC), Canada, on strategies for integrating preventive oral health into prenatal care. Methods: Twenty-four purposefully selected health care providers (13 oral health and 11 prenatal care providers) in Vancouver and Surrey BC participated in audio-recorded semistructured interviews. Interviews lasted from 31 to 61 min, were transcribed verbatim, and were analyzed using an inductive thematic analysis with N-Vivo software. Study validity was ensured via memoing, fieldnotes, member checking, and external audit. Results: Thematic analysis revealed 5 major themes: perception of integrated care, relevance of integrated prenatal oral health, strategies for achieving integrated prenatal oral health, drivers of the integration process, and barriers to integrating oral health during pregnancy. Interprofessional collaboration based on information sharing and communication was identified as a critical factor for integrated care. Oral health checks should be a component of prenatal assessments for achieving integrated prenatal oral health. Participants recommended that prenatal providers should offer oral health education and use screening questions to identify the pregnant woman's oral health needs. The establishment of referral systems was advocated, while dental assessments and oral prophylaxis via the medical services plan were proposed. The inclusion of dental providers in prenatal teams and educating health care providers on interprofessional collaboration were also supported. Conclusion: Oral health and prenatal providers in BC are positively disposed to adopting integrated preventive prenatal oral health care based on interprofessional collaborative practices. The inclusion of oral health providers in prenatal teams was suggested. Knowledge Transfer Statement: The results of this study can be used by policymakers for advocacy and decision making when planning care delivery programs for women during pregnancy. Including the suggested strategies could lead to increased access to, and utilization of, oral health services among pregnant women.